Normative Solidarity: Narratives of Solo Parent Multigenerational Caregivers in Selected Resettlement Areas in Cavite - Tabogon, Krishia Marie Villaluz; Pulgar, Andrea Nicole Dela Cruz; Maraan, Franzyne Carolyn Anorico; Rico, Feliz Nichole Rogel; Autriz, Arianne Espiritu (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2024)
This study explored the experiences of solo parents who provide simultaneous support to their minor children and senior parents in selected resettlement areas in Cavite, Philippines. Specifically, it sought to determine the reasons for their role pursuance, unravel the adversities they encountered and the coping strategies they employed, and identify their motivations for continuously juggling their multigenerational responsibilities. Using narrative analysis, the stories of eight participants selected through non-proportional quota sampling were uncovered and interpreted. Findings revealed that the high regard they placed on cultural family values and traditions drove them to become caregivers for two generations. The demands of having young and old dependents led them to face financial constraints, unfulfilled aspirations, work interference, and health-compromising behaviors associated with their role as family mediators. Social support systems and multiple sources of livelihood played a significant part in easing these burdens. Despite the hardships entailed in their household responsibilities, they managed to carry on due to the long-term care needs of family members and the positive feelings they acquired from caregiving. This may further support the need for implementation or amendment of policy programs intended to provide recognition and workplace consideration for individuals in this unique familial position.